Feeding association between benthic and nektonic Neotropical stream fishes - Teresa, Fabrício Barreto [UNESP]; Carvalho, Fernando Rogério (Sociedade Brasileira de Ictiologia, 2008)
A interação nuclear-seguidor tem sido raramente registrada entre peixes de riachos Neotropicais. Este tipo de associação foi observada em um riacho de cabeceira, no sistema do Alto rio Paraná envolvendo o cascudinho, Aspidoras fuscoguttatus, como espécie nuclear, e Knodus moenkhausii, Poecilia reticulata e Astyanax altiparanae como seus seguidores. Indivíduos de Aspidoras fuscoguttatus revolveram o substrato durante alimentação, promovendo a suspensão de sedimento. Os seguidores, por sua vez, movimentaram-se pela nuvem de partículas em suspensão, capturando itens alimentares. As particulas alimentares em suspensão parecem não ser utilizadas pelo cascudinho, mas tornam-se disponíveis para K. moenkhausii, P. reticulata e A. altiparanae. O comportamento de seguidor representa uma tática alimentar alternativa para estas espécies, reforçando a idéia geral de plasticidade comportamental entre as espécies seguidoras.

Following behaviour among Neotropical stream fishes have been scarcely reported. This type of feeding association was observed in a small stream in the upper rio Paraná system between the catfish, Aspidoras fuscoguttatus, acting as a nuclear species, and Knodus moenkhausii, Poecilia reticulata, and Astyanax altiparanae as follower species. Aspidoras fuscoguttatus individuals dug in the bottom during feeding, causing sediment suspension. Their followers picked food items in the cloud of suspended particles. Food items of sediment are no longer consumed by the catfish when in suspension, but are still available for K. moenkhausii, P. reticulata and A. altiparanae. Following behaviour is an alternative feeding tactic for these species, which reinforces the general idea of behavioural plasticity among follower species.
Keywords: Aspidoras fuscoguttatus; Feeding strategies; Interspecific interaction; Following behaviour; Southeastern Brazil